1984
DOI: 10.3109/00016358408993864
|View full text |Cite
|
Sign up to set email alerts
|

Hypodontia, hyperodontia, and double formation of primary teeth in Iceland An epidemiological study

Abstract: The aim of this study was to determine the prevalence of hypodontia, hyperodontia, and double formation of primary teeth in Icelandic children in the dental stage DS 02 (primary dentition complete). The study group comprised 927 children (498 boys and 429 girls). This was about 9% of all children aged 0-83 months in Reykjavik at the time of the registration of these anomalies, during the winter of 1978-1979. The children included those presenting for regular examinations in two health centers, children from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
27
9
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 5 publications
9
27
9
2
Order By: Relevance
“…Existing studies have focused particularly on the epidemiological descriptions of the prevalence of the condition. Thus, Grahnkn & Granath [l] found a prevalence of @4%, and in subsequent studies Ravn [2], Jarvinen & Lehtinen [3] and, later, Magnusson [4], reported prevalences of @5%, 0.9% and @5%, respectively. In these studies, attention was also given to the types of teeth most frequently affected by agenesis, and, generally, agenesis of maxillary lateral incisors was most frequent.…”
Section: Introductionmentioning
confidence: 95%
“…Existing studies have focused particularly on the epidemiological descriptions of the prevalence of the condition. Thus, Grahnkn & Granath [l] found a prevalence of @4%, and in subsequent studies Ravn [2], Jarvinen & Lehtinen [3] and, later, Magnusson [4], reported prevalences of @5%, 0.9% and @5%, respectively. In these studies, attention was also given to the types of teeth most frequently affected by agenesis, and, generally, agenesis of maxillary lateral incisors was most frequent.…”
Section: Introductionmentioning
confidence: 95%
“…Double teeth is a term that describes both gemination of one tooth, which is the partial division of a single dental germ [12,13], and fusion of two teeth, which is the partial union of two different dental germs [13,14]. The prevalence rate for double teeth in the primary dentition varies from 0.5 to 1.6% [5,9], while it has been reported to be 0.3% in the permanent dentition [15,16]. Double teeth were reported to be 75% of the cases of dental anomalies in the primary dentition, with 94% of fusions and 6% of geminations [17].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral incisors are most commonly involved [6], whereas the duplication of canines is a very rare occurrence [3]. Hypodontia is the lack of one or more teeth with a prevalence rate in the permanent dentition ranging from 0.4 to 0.9% in European populations [3][4][5][7][8][9], while it is more diffuse in Japanese children (2.4%) [10]. The prevalence rate of hypodontia of the primary teeth is smaller, and it approximates 0.3-0.8% [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the fusion takes place in the advanced stage of morph-differentiation, it may be limited to the roots, meaning the fused teeth might have separate pulp chambers and root canals [3,4]. Primary fused teeth (PFT) usually occur unilaterally [5,6] and are more common in primary than in permanent dentition [2,7,8]. They nearly always occur in the anterior region, and most often involve the mandibular lateral incisors and canines; occurrence in the posterior region is rare [9,10].…”
Section: Introductionmentioning
confidence: 99%